Supervisory Agency's Strategy in Preventing Election Vulnerability: Study on Bawaslu North Maluku Province - Mahmud Husen (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
This study aims to determine the strategy of preventing election vulnerability by the Election Supervisory Agency (Bawaslu) based on the provisions of Article 94 paragraph (1) of Law Number 7/2017 concerning Elections. Election vulnerability is an instrument of early detection of potential disturbances that can hinder the implementation of elections that are luber (direct, general, free, secret) and jurdil (honest and fair). This vulnerability includes various forms of violations such as money politics, SARA campaigns, intimidation, data manipulation, and non-neutrality of state apparatus. In the context of public organizations, strategy is understood as a structured and adaptive long-term plan, designed to effectively face external challenges. The research used a descriptive qualitative approach to gain an in-depth understanding of the role and implementation of Bawaslu's duties in the context under study. By using the Bawaslu chairperson as the key informant and Bawaslu members as additional informants, this research was able to comprehensively explore information from sources who have authority and direct experience in the implementation of election supervision. The data collection methods used, namely observation, interviews and documentation, provide strong data triangulation to increase the validity of the research results. The results showed that through civil society involvement, political education, and cross-sector cooperation, the prevention strategy implemented by Bawaslu is expected to minimize the potential for violations and strengthen participatory democracy. Thus, Bawaslu plays a strategic role in realizing quality elections that are free from various forms of vulnerability.